PENGARUH MEDIA SOSIAL WEVERSE TERHADAP PEMENUHAN KEBUTUHAN INFORMASI PADA PENGGEMAR K-POP DI WEVERSE - Zakia, Rifa; Dianita, Indria Angga; Rochimah, Haris Annisari Indah Nur (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2024)
The South Korean culture known as the Korean Wave has spread widely in the world. The popularity of Korean culture includes the entertainment industry such as dramas, movies, and music. The rapid development of technology through online media, facilitates the spread of popular culture from South Korea throughout the world. Fans of the South Korean entertainment industry, especially K-Pop fans, often engage in information seeking behavior related to their idols. One important element in fulfilling the information needs of K-Pop fans is using Weverse, which is one of the popular social media among K-Pop. This study aims to measure how much influence Weverse social media has on fulfilling the information needs of K-Pop fans in Weverse. This research applies a quantitative method with a descriptive approach. Uses and Gratification theory is applied to this research. The research subjects consist of K-Pop fans who know Weverse and have used Weverse. Data was collected by distributing questionnaires to 100 respondents in the form of Google Form. The results showed that social media variables had a large influence reaching 90.4% on the information needs of K-Pop fans in Weverse. While the remaining 9.6% has no effect on information needs. This study proves that variable X, namely social media, has a positive and significant influence on variable Y, namely information needs.